Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
( a - x )y3 - ( a - y )x3 + ( x - y )a3
= ay3 + a2y2 - ax2y - a2xy - a2y2 - a3y + a2x2 + a3x - xy3 - axy2 + x3y + ax2y + axy2 + a2xy - ax3 - a2x2
= ay( y2 +ay -x2 - ax ) - a2( y2 + ay -x2 -ax ) - xy( y2 + ay - x2 -ax ) + ax( y2 + ay -x2 -ax )
= ( y2 + ay - x2 - ax )( ay - a2 - xy + ax )
= ( y2 + xy +ay -xy -ax -x2 )[ ( y -a )a - x( y-a ) ]
= [ y( y +x +a ) - x( y + x + a )]( a - x )( a - y)
= ( y + x + a)( y -x )( a - x)( y - a)
a) \(\left(a+b\right)^3-a^3-b^3\)
\(=a^3+3a^2b+3ab^2+b^3-a^3-b^3\)
\(=3a^2b+3ab^2\)
\(=3ab\left(a+b\right)\)
b) \(\left(x+y\right)^4+x^4+y^4\)
\(=x^4+4x^3y+6x^2y^2+4xy^3+y^4+x^4+y^4\)
\(=2x^4+2y^4+4x^2y^2+4x^3y+4xy^3+2x^2y^2\)
\(=2\left(x^4+2x^2y^2+y^4\right)+4xy\left(x^2+y^2\right)+2x^2y^2\)
\(=2\left[\left(x^2+y^2\right)^2+2xy\left(x^2+y^2\right)+x^2y^2\right]\)
\(=2\left(x^2+y^2+xy\right)^2\)
a)\(4x^2-y^2+4x+1=\left(4x^2+4x+1\right)-y^2\)
\(=\left(2x+1\right)^2-y^2\)
\(=\left(2x+1-y\right)\left(2x+1+y\right)\)
b)\(x^3-x+y^3-y=\left(x^3+y^3\right)-\left(x+y\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2\right)-\left(x+y\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2-1\right)\)
= x3 + y3 + z3 + 3(x + y )(y+z)(z + x) - x3- y3 - z3
= 3(x + y)(y + z)(z + x)
a, x^4 - 5x^2 + 4
= x^4 - 4x^2- x+ 4
= x^2 . (x^2 - 4) - (x^2 - 4)
= (x^2 - 4) . (x^2 - 1)
= (x - 2) . (x + 2) . (x - 1) . (x + 1)
27x3 y - a3 b3 y = y(27x3 - a3 b3)
= y(3x - ab)(9x2 + 3xab + a2 b2)
Câu còn lại tách ra rồi họp lại là được